Homoeopathy in Treating Hypothyroidism- A Case Report (Homoeopathy for All, 2024)
Hypothyroidism is a condition  where your thyroid gland does not  produce enough thyroid hormone  which leads to slow metabolism.  Person started feeling tired, Hair  fall, weight gain, aversion to do daily activities, unable to tolerate cold  temperatures. In this article we will  see the efficacy of individualized ho moeopathic medicine CALCAREA  CARBONICA in treating the cases  of 46 years old lady.
Keywords: Homoeopathy; Hypo thyroidism; calcarea carbonica